Roles of Octopamine and Dopamine Neurons for Mediating Appetitive and Aversive Signals in Pavlovian Conditioning in Crickets - Mizunami, Makoto; Matsumoto, Yukihisa (Frontiers in Physiology, 2017)
Revealing neural systems that mediate appetite and aversive signals in associative learning is critical for understanding brain mechanisms controlling adaptive behavior in animals. In mammals, it has been shown that some classes of dopamine neurons in the midbrain mediate prediction error signals that govern the learning process and other classes of dopamine neurons control execution of learned actions. In this review, we argue that comparable aminergic systems exist in the insect brain, based on results of our studies on Pavlovian conditioning in the cricket Gryllus bimaculatus and by referring to findings in honey bees and fruit-flies. We found that administration of octopamine (the invertebrate counterpart of noradrenaline) and dopamine receptor antagonists impair conditioning to associate an olfactory or visual conditioned stimulus (CS) with water or sodium chloride solution (appetitive or aversive unconditioned stimulus, US), respectively, suggesting that specific octopamine and dopamine neurons mediate appetitive and aversive signals, respectively, in conditioning in crickets. These findings differ from those in fruit-flies that different sets of dopamine neurons mediate both appetitive and aversive signals, suggesting diversity in neurotransmitters mediating appetitive signals in insects. We also found evidence of “blocking” and “auto-blocking” phenomena, which suggested that the prediction error, the discrepancy between actual US and predicted US, governs conditioning in crickets and that octopamine neurons mediate prediction error signals for appetitive US. Our studies also showed that activation of octopamine and dopamine neurons is needed for execution of an appetitive conditioned response (CR) and an aversive CR, respectively, and we thus proposed that these neurons mediate US prediction signals that drive appetitive and aversive CRs, respectively. Our findings suggest that the basic principles of functioning of aminergic systems in associative learning, i.e., to mediate prediction error signals for conditioning and US prediction signals for execution of CR, are conserved among insects and mammals, on account of the fact that the organization of the insect brain is much simpler than that of the mammalian brain. Further investigation of aminergic systems that govern associative learning in insects should lead to a better understanding of commonalities and diversities of computational rules underlying associative learning in animals.